Effect of hydroxocobalamin on nimodipine-induced refractory vasoplegia in a patient with liver cirrhosis: a case report - Sally You (Journal of Neurocritical Care)
Background We report a case of severe vasoplegia that was unresponsive to triple vasopressor therapy but showed marked hemodynamic improvement following intravenous hydroxocobalamin administration in a patient with underlying cirrhosis. Case Report A 63-year-old Asian woman with no remarkable medical history presented with a 1-week history of headaches and neck stiffness. Imaging revealed an aneurysmal subarachnoid hemorrhage. Shortly after initiating oral nimodipine, she developed profound hypotension that was refractory to fluid resuscitation and high-dose triple vasopressor support. After excluding other causes of distributive shock, she received 5 g of intravenous hydroxocobalamin for suspected nimodipine-induced vasoplegia, which resulted in the rapid stabilization of blood pressure. No adverse effects were observed apart from transient chromaturia. Subsequent workup revealed cirrhosis secondary to chronic hepatitis B infection. Conclusion Nimodipine remains a mainstay in the management of subarachnoid hemorrhage to prevent delayed cerebral ischemia; however, severe catecholamine-resistant hypotension is an uncommon adverse effect, particularly in patients with impaired hepatic metabolism. Drug-induced vasoplegia should be considered in cases of unexplained vasodilatory shock following nimodipine administration. This case illustrates the successful use of hydroxocobalamin as rescue therapy under such circumstances.